A method for preparing a strong organic solvent-resistant polysulfone separation membrane by super cross-linking
Preparation of polysulfone separation membranes that are resistant to strong organic solvents through supercrosslinking technology solves the problem of the existing membrane being undustable in a strong organic solvent environment, achieves high throughput and long-term stability, and simplifies process conditions and is suitable for scale Chemical production.
Patent Information
- Application Number
- CN202210555915.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-05-19
AI Technical Summary
The existing polymer membrane is not durable under a strong organic solvent environment, and the preparation method has defects such as narrow application scope, poor solvent resistance, single polymer species, difficult synthesis, high price, and complex membrane making steps, making it difficult to produce on a large scale. and harmful to the environment.
Polysulfone separation membrane with strong resistance to organic solvents was prepared by supercrosslinking, using polysulfone as raw material and nanoparticles as additives, and non-solvent-induced phase conversion method. The polysulfone molecular chains were supercrossed in a solution containing a crosslinking agent. The combination reaction forms a polysulfone separation membrane that is resistant to strong organic solvents.
The stable operation of the polysulfone membrane under strong organic solvent conditions is achieved, the problem of existing membranes is overcome, the flux and long-term stability of the membrane are improved, and the process conditions are gentle and the steps are simple, which is suitable for large-scale production.
Smart Images

Figure CN114768559B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of special separation materials, and particularly relates to a cross-linking preparation method for a strong organic solvent-resistant polysulfone separation membrane. Background Art
[0002] Polysulfone membrane refers to a membrane with screening function made of a polymer compound with repeated sulfone groups and arylene groups in the main chain. Polysulfone usually refers to three representative types, including ordinary bisphenol A polysulfone, polyaryl sulfone and polyether sulfone. The sulfur atom of polysulfone is in the highest oxidation state. The conjugation effect of the sulfone group makes it have excellent antioxidant and thermal stability. The ether chain improves the toughness of polysulfone, and the benzene ring improves the mechanical strength and modulus. All chains in the molecule are not easy to hydrolyze and are acid and alkali resistant. It is easily soluble in polar solvents such as N, N-dimethylacetamide. After adding porogens to make a casting liquid, the membrane is made into tubular, plate-and-frame, roll and hollow fiber components. Polysulfone can be made into a good support membrane for ultrafiltration membranes and composite membranes, and can also be used to prepare microfiltration membranes, nanofiltration membranes and reverse osmosis membranes. It is widely used in nuclear fuel and metal refining, gas separation, seawater desalination, ultrapure water preparation, waste treatment, medicine, food, agriculture, chemical industry and other fields.
[0003] In recent years, organic solvents have been widely used in the fields of paint, medicine, chemical industry, printing, etc. as raw materials, reaction media and cleaning agents. They are of many types, large amounts and involve a wide range of industries. Being able to recycle and reuse them is of great significance for saving resources, reducing energy consumption and protecting the environment. The traditional recovery of organic solvents is mainly distillation, extraction and absorption, which has the disadvantages of high energy consumption and large solvent loss. Compared with traditional processes, membrane separation technology has low energy consumption and no solvent loss, and has greater development prospects in the separation of substances in organic solvent environments. The separation of substances in different organic solvent environments puts higher requirements on the tolerance and stability of membrane materials. However, the polymer membranes currently used are generally prepared by dissolving organic polymers in organic solvents, which means that the polymer membranes prepared by this method are generally not resistant to strong organic solvents. In terms of solving the problem of organic polymer membranes being resistant to strong organic solvents, only a few patents report the preparation of strong organic solvent resistant polymer membranes by synthesizing high molecular polymers with solvent tolerance or interfacial polymerization, but these methods have the disadvantages of narrow application range, poor resistance to strong organic solvents, single polymer type, difficult polymer synthesis, high polymer price, complex membrane preparation steps, difficulty in large-scale production and environmental damage, etc. Therefore, it is necessary to further develop membranes with commercial application potential and stable operation in strong organic solvents. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention proposes a method for preparing a polysulfone separation membrane resistant to strong organic solvents by hyper-crosslinking. The method uses polysulfone as a raw material and nanoparticles as an additive to prepare a polysulfone separation membrane by non-solvent induced phase transformation. The polysulfone molecular chain undergoes a hyper-crosslinking reaction in a solution containing a crosslinking agent, and after cleaning and activation, a polysulfone separation membrane resistant to strong organic solvents is finally formed. The cross-linked polysulfone membrane exhibits good resistance to strong organic solvents, overcoming the problem that the existing polysulfone membrane cannot be used under strong organic solvent conditions.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a strong organic solvent-resistant polysulfone separation membrane by hypercrosslinking, the method comprising the following steps:
[0007] (1) Preparation of polysulfone separation membrane: adding nanoparticles of porous nanomaterials accounting for 0.01 to 10 wt% of the mass ratio of the casting solution to a strongly polar aprotic organic solvent, and ultrasonicating to uniformly disperse the nanoparticles in the solvent; then adding bisphenol A type polysulfone accounting for 15 to 30 wt% of the mass ratio of the casting solution, stirring to uniformly dissolve it to obtain a casting solution, and preparing a polysulfone separation membrane by a solution phase inversion method;
[0008] (2) preparing a crosslinking agent solution: dissolving the catalyst in the crosslinking agent to prepare a crosslinking agent solution;
[0009] (3) Cross-linking reaction: The prepared polysulfone separation membrane is transferred to a cross-linking agent solution and heated in an oil bath, so that the cross-linking agent undergoes an electrophilic substitution reaction with the isopropylbenzene structure in the polysulfone molecular chain to obtain a cross-linked polysulfone separation membrane; the cross-linking agent is a substance that can undergo an electrophilic reaction with an electrophilic reagent; the cross-linking reaction equation is as follows:
[0010]
[0011] (4) Post-treatment: The cross-linked polysulfone membrane is cleaned with an acid solution or an ethanol solution to obtain a polysulfone separation membrane resistant to strong organic solvents.
[0012] Bisphenol A polysulfone is currently the most commonly used material for preparing commercial polysulfone membranes, and the benzene ring in its monomer has multiple reaction sites, which is more conducive to the occurrence of electrophilic substitution reactions. At the same time, it is simple to synthesize, easy to form membranes, can be mass-produced, has excellent mechanical properties, strong processability, and a wide range of applications.
[0013] Furthermore, the nanoparticles of the porous nanomaterial are any one of porous MOF materials including MIL series, ZIF series, UiO series, COF, zeolite, carbon nanotubes, and graphene oxide. Among them, MIL-88A has the best effect. It has good porosity, simple synthesis, good thermal stability, and contains Fe ions, which can further catalyze the cross-linking reaction. If the amount of nanoparticles added is too low, the membrane performance is not good. If the amount of nanoparticles added is too high, the membrane performance will decrease.
[0014] Furthermore, the highly polar aprotic organic solvent is any one of N-methylpyrrolidone, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide. Among them, N-methylpyrrolidone has the best effect because it has good solubility for polysulfone and can shorten the time for preparing the casting solution.
[0015] Furthermore, the crosslinking agent is any one of methylal, trimethoxymethane, trimethyl orthoacetate, and triethyl orthoacetate. The best effect is methylal, in which the oxygen atom contains an unshared electron pair, which can react with an electrophilic reagent to generate a carbon cation, and then react with a benzene ring to achieve a crosslinking effect.
[0016] Furthermore, the catalyst is any one of halogenated acetic acid, aluminum trichloride, ferric trichloride, and tin tetrachloride. The catalyst can accept unpaired electrons in the cross-linking agent, thereby making the cross-linking agent positively charged and capable of electrophilic reaction with the benzene ring.
[0017] Furthermore, the crosslinking agent solution is prepared by dissolving 1 to 20 g of catalyst in each milliliter of crosslinking agent. In the crosslinking agent solution, if the catalyst concentration is too low, the crosslinking reaction is difficult to occur. If the catalyst concentration is too high, the solution is oversaturated, and the catalyst precipitates.
[0018] In order to clean the polysulfone separation membrane more thoroughly, it is cleaned 1 to 3 times with an acidic solution or ethanol solution with a pH value less than 2, and then immersed in ethanol for 1 hour. Ethanol can dissolve the catalyst and clean the catalyst remaining on the membrane surface, thereby obtaining a polysulfone separation membrane resistant to strong organic solvents.
[0019] A strong organic solvent resistant polysulfone separation membrane obtained by the preparation method.
[0020] The beneficial effects of the present invention are as follows:
[0021] (1) The present invention provides a method for preparing a polysulfone separation membrane resistant to strong organic solvents by means of a hypercrosslinking reaction between benzene rings. Compared with most current polysulfone membranes that only undergo crosslinking reactions on the surface, the method provided by the present invention can allow crosslinking reactions to occur on the surface and in the internal porous structure of the membrane, thereby giving the polysulfone the property of being resistant to strong organic solvents.
[0022] (2) This method only requires the addition of nanomaterials to make the cross-linked polysulfone membrane have a higher flux, thus overcoming the defect of using other soluble additives to prepare the polysulfone membrane in the method to form an ultra-thick dense layer, and optimizing the process flow.
[0023] (3) The polysulfone membrane prepared by the method of the present invention is immersed in strong solvents such as dimethylformamide, dimethylacetamide, N-methylpyrrolidone and conventional solvents such as toluene and chloroform for one month, and the membrane structure remains unchanged.
[0024] (4) The cross-linking reaction conditions used in the present invention are mild, the steps are simple and the versatility is strong, which is conducive to the large-scale production of polysulfone separation membranes resistant to strong organic solvents, and provides the possibility for the separation application of polysulfone separation membranes in strong organic solvents.
[0025] (5) The strong organic solvent-resistant polysulfone separation membrane prepared by the method of the present invention has a flux of more than 0.5 L / m2.h.bar in N-methylpyrrolidone, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, and 1,4-dioxane. After 60 hours of continuous operation, the flux attenuation is less than 20%. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The electron microscope pictures are of the membrane surface morphology of the polysulfone separation membranes obtained under different conditions in Comparative Example 1 and Examples 1, 2, 3, and 4.
[0027] Figure 2 The electron microscope pictures are of the membrane cross-section morphology of the polysulfone separation membranes obtained under different conditions in Comparative Example 1 and Examples 1, 2, 3, and 4.
[0028] Figure 3 This is an electron microscope picture of the surface morphology of the membrane prepared in Example 1 after solvent treatment.
[0029] Figure 4 It is a curve chart of the changes in the infrared spectrum of the membrane prepared in Example 1 before and after cross-linking.
[0030] Figure 5 It is a graph of flux data of the membrane prepared in Example 1 in various strong organic solvents.
[0031] Figure 6 The figure shows the rejection rate of Congo red dye and the flux data during the rejection process of the membrane prepared in Example 1 in DMF solvent.
[0032] Figure 7 The figure shows the retention rate of Congo red dye and the flux data during the retention process of the membrane prepared in Example 2 in DMAC solvent.
[0033] Figure 8The figure shows the rejection rate of the membrane prepared in Example 3 for Direct Red 227 dye in DMF solvent and the flux data during the rejection process. DETAILED DESCRIPTION
[0034] The present invention will be described in detail below based on the accompanying drawings and preferred embodiments, and the purpose and effects of the present invention will become more clear. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] Example 1
[0036] (1) Preparation of polysulfone separation membrane: 1.8 wt% of MIL-88A nanoparticles were added to N-methylpyrrolidone solvent and ultrasonicated for 30 min. Then 15 wt% of bisphenol A polysulfone was added and stirred until uniformly dissolved. After standing for a period of time until the bubbles disappeared completely, the membrane was coated on a clean glass plate using a 150 μm thick scraper and then immersed in water to form a membrane. After the solvent exchange was complete, the formed film was taken out and dried to obtain a polysulfone separation membrane. Its structure was characterized by electron microscopy. See attached figure. Figure 1 The original film picture in the upper left corner.
[0037] (2) Preparation of crosslinking agent solution: Dissolve 10 g of ferric chloride in 10 ml of formaldehyde dimethyl acetal crosslinking agent to prepare a crosslinking agent solution.
[0038] (3) Cross-linking reaction: The prepared membrane is then immersed in the cross-linking agent solution and reacted in an oil bath at 60° C. for 12 h. After the reaction, the membrane is taken out;
[0039] (4) Post-treatment: The membrane was rinsed with ethanol three times, then taken out and soaked in ethanol for 1 hour to obtain a strong organic solvent resistant polysulfone separation membrane, and its structure was characterized by electron microscopy. The cross-linking reaction equation is as follows:
[0040]
[0041] Example 2
[0042] (1) Preparation of polysulfone separation membrane: 0.1 wt% ZIF-8 nanoparticles were added to N-methylpyrrolidone solvent and ultrasonicated for 30 min. Then 15 wt% bisphenol A polysulfone was added and stirred until uniformly dissolved. After standing for a period of time, the membrane was coated on a clean glass plate with a 150 μm thick scraper and then immersed in water for phase conversion to form a membrane. After the solvent exchange was complete, the formed film was taken out and dried to obtain a polysulfone separation membrane, and its structure was characterized by electron microscopy.
[0043] (2) Preparation of crosslinking agent solution: Dissolve 20 g of aluminum chloride in 10 ml of formaldehyde dimethyl acetal crosslinking agent to prepare a crosslinking agent solution.
[0044] (3) Cross-linking reaction: The prepared membrane is then immersed in the cross-linking agent solution and reacted in an oil bath at 60° C. for 24 h. The membrane is then taken out after the reaction;
[0045] (4) Post-treatment: The membrane was rinsed with ethanol three times and then soaked in ethanol for 1 h to obtain a strong organic solvent-resistant polysulfone separation membrane. Its structure was characterized by electron microscopy.
[0046] Example 3
[0047] (1) Preparation of polysulfone separation membrane: 0.01 wt% of graphene oxide nanosheets were added to N-methylpyrrolidone solvent and ultrasonicated for 30 min. Then 30 wt% of bisphenol A polysulfone was added and stirred until uniformly dissolved. After standing for a period of time, the membrane was coated on a clean glass plate with a scraper having a thickness of 150 μm and then immersed in water to form a membrane. After the solvent exchange was complete, the formed film was taken out and dried to obtain a polysulfone separation membrane, and its structure was characterized by electron microscopy.
[0048] (2) Preparation of crosslinking agent solution: Dissolve 20 g of ferric chloride in 10 ml of formaldehyde dimethyl acetal crosslinking agent to prepare a crosslinking agent solution.
[0049] (3) Cross-linking reaction: The prepared membrane is then immersed in the cross-linking agent solution and reacted in an oil bath at 80° C. for 6 h. After the reaction, the membrane is taken out;
[0050] (4) Post-treatment: The membrane was washed with acid solution for 5 times, and then soaked in ethanol for 1 hour to obtain a strong organic solvent resistant polysulfone separation membrane. Its structure was characterized by electron microscopy.
[0051] Example 4
[0052] (1) Preparation of polysulfone separation membrane: 0.01 wt% COF was added to N-methylpyrrolidone solvent and ultrasonicated for 30 min. Then 30 wt% bisphenol A polysulfone was added and stirred until uniformly dissolved. After standing for a period of time, the membrane was coated on a clean glass plate with a scraper of 150 μm thickness and then immersed in water to form a membrane. After the solvent exchange was complete, the formed film was taken out and dried to obtain a polysulfone separation membrane, and its structure was characterized by electron microscopy.
[0053] (2) Preparation of crosslinking agent solution: Dissolve 10 g of ferric chloride in 10 ml of formaldehyde dimethyl acetal crosslinking agent to prepare a crosslinking agent solution.
[0054] (3) Cross-linking reaction: the prepared membrane is then immersed in the cross-linking agent solution, heated in an oil bath at 100° C. for 30 min, and the membrane is taken out after the reaction;
[0055] (4) Post-treatment: The membrane was rinsed with ethanol once, and then soaked in ethanol for 1 h to obtain a strong organic solvent-resistant polysulfone separation membrane. Its structure was characterized by electron microscopy.
[0056] Example 5
[0057] (1) Preparation of polysulfone separation membrane: 10 wt% zeolite was added to N-methylpyrrolidone solvent and ultrasonicated for 30 min. Then 15 wt% bisphenol A polysulfone was added and stirred until uniformly dissolved. After standing for a period of time, the membrane was coated on a clean glass plate with a scraper having a thickness of 150 μm and then immersed in water to form a membrane. After the solvent exchange was complete, the formed film was taken out and dried to obtain a polysulfone separation membrane, and its structure was characterized by electron microscopy.
[0058] (2) Preparation of crosslinking agent solution: Dissolve 10 g of tin tetrachloride in 10 ml of trimethyl orthoacetate crosslinking agent to prepare a crosslinking agent solution.
[0059] (3) Cross-linking reaction: The prepared membrane is then immersed in the cross-linking agent solution and heated in an oil bath at 60° C. for 12 h. After the reaction, the membrane is taken out;
[0060] (4) Post-treatment: The membrane was washed three times with an acid solution of pH = 1, and then soaked in ethanol for 1 hour to obtain a strong organic solvent-resistant polysulfone separation membrane. Its structure was characterized by electron microscopy.
[0061] Example 6
[0062] (1) Preparation of polysulfone separation membrane: 0.1 wt% carbon nanotube nanoparticles were added to N-methylpyrrolidone solvent and ultrasonicated for 30 min. Then 15 wt% bisphenol A polysulfone was added and stirred until uniformly dissolved. After standing for a period of time, the membrane was coated on a clean glass plate with a scraper having a thickness of 150 μm and then immersed in water to form a membrane. After the solvent exchange was complete, the formed film was taken out and dried to obtain a polysulfone separation membrane, and its structure was characterized by electron microscopy.
[0063] (2) Preparation of crosslinking agent solution: Dissolve 40 g of chloroacetic acid in 2 ml of triethyl orthoacetate crosslinking agent to prepare a crosslinking agent solution.
[0064] (3) Cross-linking reaction: The prepared membrane is then immersed in the cross-linking agent solution and heated in an oil bath at 80° C. for 9 h. After the reaction, the membrane is taken out;
[0065] (4) Post-treatment: The membrane was washed three times with ethanol and then soaked in ethanol for 1 h to obtain a strong organic solvent-resistant polysulfone separation membrane. Its structure was characterized by electron microscopy.
[0066] Example 7
[0067] (1) Preparation of polysulfone separation membrane: 0.1 wt% UIO-66 nanoparticles were added to N-methylpyrrolidone solvent and ultrasonicated for 30 min. Then 15 wt% bisphenol A polysulfone was added and stirred until uniformly dissolved. After standing for a period of time, the membrane was coated on a clean glass plate with a 150 μm thick scraper and then immersed in water to form a membrane. After the solvent exchange was complete, the formed film was taken out and dried to obtain a polysulfone separation membrane, and its structure was characterized by electron microscopy.
[0068] (2) Preparation of crosslinking agent solution: Dissolve 10 g of ferric chloride in 10 ml of trimethoxymethane crosslinking agent to prepare a crosslinking agent solution.
[0069] (3) Cross-linking reaction: The prepared membrane is then immersed in the cross-linking agent solution and heated in an oil bath at 80° C. for 12 h. After the reaction, the membrane is taken out;
[0070] (4) Post-treatment: The membrane was washed with ethanol three times and then soaked in ethanol for 1 h to obtain a strong organic solvent-resistant polysulfone separation membrane. Its structure was characterized by electron microscopy.
[0071] Comparative Example 1
[0072] (1) Preparation of polysulfone separation membrane: 0.6 wt% of MIL-88A nanoparticles were added to N-methylpyrrolidone solvent and ultrasonicated for 30 min. Then 15 wt% of bisphenol A polysulfone was added and stirred until uniformly dissolved. After standing for a period of time, the membrane was coated on a clean glass plate using a 150 μm thick scraper and then immersed in water for phase conversion to form a membrane. After the solvent exchange was complete, the formed film was taken out and dried to obtain a polysulfone separation membrane. Its surface structure was characterized by electron microscopy.
[0073] The surface electron microscopy images of the polysulfone separation membranes obtained in Examples 1, 2, 3, 4 and Comparative Example 1 are as follows: Figure 1 As shown in the figure, at different reaction temperatures and reaction times, the morphology of the membrane after cross-linking is basically the same as that before cross-linking, indicating that the cross-linking result obtained by this cross-linking method is relatively stable and the requirements for reaction conditions are not harsh. The cross-sectional electron microscopy images of the polysulfone separation membranes obtained in Examples 1, 2, 3, 4 and Comparative Example 1 are shown in the figure. Figure 2 As shown, the thickness of the dense layer becomes thinner, thereby overcoming the defect of forming an ultra-thick dense layer in the method of preparing a polysulfone membrane using other soluble additives.
[0074] Solvent resistance test:
[0075] (1) The strong organic solvent resistant polysulfone separation membranes prepared in all the above examples were subjected to an immersion test, specifically:
[0076] The prepared strong organic solvent-resistant polysulfone separation membrane was immersed in N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMAC), chloroform, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), and 1,4-dioxane (DOX) at room temperature for one month, and its structure was characterized by electron microscopy. Figure 3 Electron micrographs of the polysulfone separation membrane of Example 1 after being immersed in various strong organic solvents are given. It can be seen from the figure that the membrane has good long-term stability in strong organic solvents. The membrane is easily soluble in N-methylpyrrolidone before cross-linking, but insoluble after cross-linking, indicating that cross-linking is successful. Cross-linking can increase the membrane's tolerance to strong organic solvents.
[0077] (2) The strong organic solvent resistant polysulfone separation membrane obtained in Example 1 was subjected to infrared testing. The test results are as follows: Figure 4 As shown in the figure, it can be seen that the characteristic peak of the benzene ring changes after cross-linking, and the CH out-of-plane bending vibration on the benzene ring changes, indicating that the cross-linking reaction occurs successfully.
[0078] (3) The flux of the strong organic solvent resistant polysulfone separation membrane obtained in Example 1 was tested. Figure 5 As shown in the figure, it can be seen that the polysulfone separation membrane obtained in Example 1 is resistant to strong organic solvents and can be used in these solvents.
[0079] (4) Congo red was dissolved in dimethylformamide (DMF) and tested with the strong organic solvent resistant polysulfone separation membrane prepared in Example 1. The test results are as follows: Figure 6 As shown, the Congo red rejection rate and DMF flux of the polysulfone separation membrane do not change much with the test time, indicating that the polysulfone separation membrane obtained in Example 1 has long-term stability.
[0080] (5) Congo red was dissolved in dimethylacetamide (DMAC) and tested with the strong organic solvent resistant polysulfone separation membrane prepared in Example 2. The test results are as follows: Figure 7 As shown, the Congo red rejection rate and DMAC flux of the polysulfone separation membrane do not change much with the test time, indicating that the polysulfone separation membrane obtained in Example 2 has long-term stability.
[0081] (6) Direct Red 227 was dissolved in dimethylformamide (DMF) and tested using the strong organic solvent resistant polysulfone separation membrane prepared in Example 3. The test results are as follows: Figure 8 As shown, the retention rate of Direct Red 227 and the DMF flux of the polysulfone separation membrane do not change much with the test time, indicating that the polysulfone separation membrane obtained in Example 3 has long-term stability.
[0082] Those skilled in the art can understand that the above are only preferred examples of the invention and are not intended to limit the invention. Although the invention is described in detail with reference to the above examples, those skilled in the art can still modify the technical solutions recorded in the above examples or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, etc. made within the spirit and principle of the invention shall be included in the protection scope of the invention.
Claims
1. A method for preparing a strong organic solvent-resistant polysulfone separation membrane by hypercrosslinking, characterized in that: The method comprises the following steps: (1) Preparation of polysulfone separation membrane: adding nanoparticles of porous nanomaterials accounting for 0.01-10 wt% of the mass ratio of the casting solution to a strongly polar aprotic organic solvent, and ultrasonicating to evenly disperse the nanoparticles in the solvent; then adding bisphenol A type polysulfone accounting for 15-30 wt% of the mass ratio of the casting solution, stirring to evenly dissolve it to obtain a casting solution, and preparing a polysulfone separation membrane by a solution phase inversion method; the nanoparticles of the porous nanomaterial are porous MOF materials or COFs including MIL series, ZIF series, and UiO series; the strongly polar aprotic organic solvent is any one of N-methylpyrrolidone, dimethylacetamide, and dimethyl sulfoxide; (2) preparing a cross-linking agent solution: dissolving the catalyst in the cross-linking agent to prepare a cross-linking agent solution; (3) Cross-linking reaction: the prepared polysulfone separation membrane is transferred to a cross-linking agent solution and heated in an oil bath, so that the cross-linking agent undergoes an electrophilic substitution reaction with the isopropylbenzene structure in the polysulfone molecular chain to obtain a cross-linked polysulfone separation membrane; the cross-linking agent is a substance that can undergo an electrophilic reaction with an electrophilic reagent; the cross-linking reaction time is 30 min to 24 h, and the reaction temperature is 60 to 100 °C; (4) Post-treatment: The cross-linked polysulfone separation membrane is cleaned and activated with an acid solution or an ethanol solution to obtain a polysulfone separation membrane resistant to strong organic solvents; The cross-linking agent solution is prepared by dissolving 1 to 20 g of catalyst in each milliliter of cross-linking agent; The cross-linking agent is any one of trimethoxymethane, trimethyl orthoacetate, and triethyl orthoacetate; The catalyst is tin tetrachloride; In the step (4), the cross-linked polysulfone separation membrane is firstly cleaned 1 to 3 times with an acidic solution or an ethanol solution with a pH value less than 2, and then immersed in ethanol for 1 hour to obtain a strong organic solvent resistant polysulfone separation membrane.
2. A polysulfone separation membrane resistant to strong organic solvents prepared by the method for preparing a polysulfone separation membrane resistant to strong organic solvents by hypercrosslinking as claimed in claim 1.
Citation Information
Patent Citations
Method for modifying polyethersulfone ultrafiltration membrane by hollow Fe3O4 (ferroferric oxide) nanoparticle
CN106621830A
Method for preparing solvent-resistant and acid-alkali-resistant homoporous membrane through crosslinking
CN112295424A